First-principles study of plutonium adsorption on perfect and defective graphene and hexagonal boron nitride. (25th May 2018) - Li, Shujing; Zhou, Mei; Li, Menglei; Wang, Xiaohui; Zheng, Fawei; Zhang, Ping
Abstract: The adsorption of the Pu atom on perfect and defective graphene and hexagonal boron nitride ( h -BN) sheet has been systematically investigated by using first-principles calculations. Pu atom is most likely to trap at the hollow site in pure graphene, and the energy barrier is as high as 78.3 meV. For ideal h -BN, the top site of the boron atom is the most stable adsorption site for adatom Pu, and the maximal energy barrier is only 12 meV. Comparing Pu on pure graphene and h -BN sheet, Pu atom is easy to migrate on the surface of ideal h -BN at room temperature, while it is bound to perfect graphene. Besides, Pu atom adsorbed on defective graphene and h -BN sheet, with large adsorption energies in the range of 2.66 ∼ 14.95 eV, is more stable than that on pure graphene and h -BN sheet. We have also found that all the adsorption systems are spin-polarized with the largest magnetic moments of Pu to be 7.67 μ B on graphene and 6.71 μ B on h -BN with a single vacancy of N atom. These findings suggest that graphene and h -BN two-dimensional materials can be effectively applied in the growth of high-quality plutonium single crystal thin films, as well as in nuclear waste recovery.